Simultaneous delivery of several antimicrobial drugs from multi‐compartment glycerol‐silicone membranes. Issue 32 (31st March 2021) - Mazurek, Piotr; Yuusuf, Nuura A.; Silau, Harald; Mordhorst, Hanne; Pamp, Sünje J.; Brook, Michael A.; Skov, Anne L.
Abstract: Combining drugs is an efficient tool in fighting bacterial infections. It has been proven to enable an increased antimicrobial activity compared to mono‐drug therapies. Current commercial dressings for treatment of infected wounds provide delivery of one drug only. Therefore, there is an obvious need to develop a technology enabling incorporation and release of two and more actives. Ideally, such technology should prevent potential cross‐reactions between the drugs during long‐term storage. Here, a concept of drug compartmentalization within distinct glycerol domains of glycerol‐silicone elastomer membranes is presented. Multiple drugs are encapsulated within different types of glycerol domains hampering any cross‐reactions. The drugs are simultaneously released upon contact with aqueous media and the release kinetics can be precisely adjusted by tuning various material parameters, such as glycerol content and membrane thickness. Ultimately, the drug release capabilities and the antimicrobial potential are evaluated against a variety of bacteria in an agar diffusion assay. The membranes are proven effective against different bacterial species, which confirms the efficiency of release even at minimum moisture levels. The glycerol‐silicone platform technology enables delivery of virtually unlimited combinations of drugs from different drug families (e.g., antimicrobial, anti‐inflammatory, and pain relief agents) facilitating new ways of treating wound disorders. Abstract : Multi‐compartment glycerol‐silicone elastomeric membranes are a platform technology enabling compartmentalization, storage, and controlled release of several active substances such as antimicrobial, anti‐inflammatory, and pain relief agents. The emulsification process is fully controllable and thus it enables producing elastomers with virtually unlimited number of drug combinations facilitating new opportunities for the combination drug therapy, for example, in topical treatment of chronic wounds.